Investigating the Effect of Sulfate Attack on Compressive Strength of Recycled Aggregate Concrete - Tayeh, Bassam A.; Arafa, Mohamed; Alqedra, Mamoun; Shihada, Samir; Hanoona, Hesham (International Journal of Sustainable Construction Engineering and Technology, 2017)
This research aimed at studying the effect of sulfate attack on the compressive concrete strength with various percentages of recycled aggregate replacements (0%, 30%, 60% and 100%). Water cement ratio (0.42) are used, MgSO4 solution was used with two concentration (6% and 9 %) to represent the effect of sulfate attack on the concrete compressive strength. The experimental tests focused on physical properties of recycled aggregate; density, unit weight, sieve analysis, Los Angles test and specific gravity. Tests have also been performed on 108 concrete cubes samples at 7 days, 14 days and 28 days for compressive strength. The results of Â compressive strength at 28 days using (0%, 30%, 60% and 100%) recycled aggregate are (330, 280, 266 and 244) Kg/cm2 respectively, with reduction in compressive strength was (15.2%, 19.4% and 26%) Â for replacement ratio (30%, 60% and 100%) respectively. MgSO4 solution has an effect on compressive strength after 90 days of immersion in 6% and 9% concentrated of MgSO4 solution. The results of this study show that the reduction in compressive strength using recycled aggregate is more sensitive against the sulfate attack compared with natural aggregate.